Stereotactic fractionated irradiation of optic nerve sheath meningioma: a new treatment alternative. Issue 11 (1st November 2002) - Pitz, S; Becker, G; Schiefer, U; Wilhelm, H; Jeremic, B; Bamberg, M; Zrenner, E
Abstract : Background: Primary optic nerve sheath meningioma (ONSM) is a rare but almost invariably blinding tumour when its natural history is observed in a "wait and see" strategy. Surgery has hitherto only been advocated in case of progressive disease involving intracranial structures, as it leads to iatrogenic blindness in the overwhelming majority of cases. Therefore, treatment options bearing lesser risk of functional deterioration are highly desirable, both in cases of intracranial involvement as well as during earlier phases of the disease which are currently generally left untreated. The authors report the outcome of the largest series of patients to date treated by stereotactic fractionated irradiation as a new treatment approach in ONSM at all stages. Methods: 15 patients (16 nerves) underwent stereotactic fractionated conformal irradiation with a total dose of 54 Gy, using standard fractionation. Main outcome parameters included visual acuity and visual field, as well as three dimensional remission as documented by imaging. Results: Tumour control was confirmed in all 15 patients undergoing stereotactic fractionated conformal irradiation (mean follow up 37 (range 12–71) months). No patient developed functional deterioration during or after treatment. Moreover, visual acuity improved by more than two lines in one patient and the visual field improved in six cases. Visual outcome in the other patients remained unchanged. There were no significant side effects of radiation therapy. Conclusion: These data provide convincing evidence that stereotactic fractionated conformal irradiation is an effective treatment option for primary ONSM with minimal treatment related morbidity. It should therefore be considered as therapeutic option both in early stage ONSM where surgery cannot be justified as well as in later stages, where surgery is so far considered the first line approach.